Evolusi Madrasah Tafsir Al-Qur’an di Mesir: Penelusuran Era dan Tipologi Media - Fikriyati, Ulya (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Humans are always obsessed with a newness. They are trying to display and apply a newness in various aspects of life. The same practice is also happen in Egyptian exegesis school. Although not as old as the exegesis school in Mecca, Medina, Kufa and Basra, the exegesis school in Egypt are interesting to be examined in reason of its exist from the classical to the contemporary era. The stretched era definitely requires an evolution. This article explores the evolution of media used in delivering Qur'anic interpretation and commentaries along these eras in Egypt. Using a historical approach, the evolution of exegesis school in Egypt can be mapped into three main phases. The classical phase uses the oral and written media (manuscripts), the transitional phase uses printing (magazines/printed books) and electronic media (radio / television), and the contemporary phase uses digital media.